Analisis Peran Lembaga Negara dalam Penegakan HAM di Indonesia - Adinda Melisa Putri; Alya Deska Safira; Auliah Ramayani; Muhammad Rifky Rizani; Muhammad Dandy Pratama; Sayit Bandung Bondowoso (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This paper is intended to analyze how institutions play a role as government institutions in upholding human rights, which focuses on human rights enforcement as reviewed from the performance of Komnas HAM institutions, the Ombudsman and other institutions, as well as the challenges faced in upholding human rights advocacy in Indonesia. Human rights problems are not a new problem in Indonesia, the many human rights violations in Indonesia if this problem continues to be left without evaluation and solutions, it will result in prosecution to the Government in order to solve the existing problems. Even after the reform, human rights violations continue to occur and are signaled in Indonesia, proving the inadequacy of the role of State Institutions to solve problems of human rights violations in Indonesia and ensure real security and protection of justice for the Indonesian people.